Fabrication of metal-supramolecular polymers of FeL/carbon nanomaterials with enhanced electrochromic properties. (29th September 2020) - Qu, Dawei; Liu, Liwei; Li, Xin; Chen, Kun; Zheng, Yiping; Xue, Yumiao; Chen, Guangming
Abstract: The metal-supramolecular polymers, with emerging state-of-the-art electrochromic materials (ECMs), have witnessed explosive developments due to wide promising applications in industry and military. Here, we report novel composites of metal-supramolecular polymer FeL (combining 1, 4-bis(2, 2':6′, 2″-tribipyridin-4′-yl) benzene (L) with Fe) with 0D to 2D functionalized carbon nanomaterials (fullerene (C60 ), single-walled carbon nanotube (SWCNT) and graphene oxide (GO)), showing significant improved cyclic stability and response time. FTIR spectra indicate that a strong interfacial interaction occurred between FeL and carbon nanomaterials. SEM image clearly shows that the addition of carbon nanomaterials results in a large number of homogeneous micro-pores on the film surface morphology, especially for the FeL/SWCNT, which contributes to the ion migration during the electrochromic process. Consequently, the order of electrochemical activity of the as-prepared composites follows the order of FeL/SWCNT > FeL/C60  > FeL/GO > FeL. Compared with the pristine FeL, the three composites exhibit obviously improved cyclic stability and response time. In particular, the FeL/SWCNT composite displays the optimal electrochromic properties with the bleaching time of 1 s, and the coloring time of 0.9 s, and the highest cyclic stability. Graphical abstract: Image 1